2018
DOI: 10.1177/1178630218792861
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Variation of Particulate Matter(PM2.5) Concentrations and Its Health Impacts in a Mega City, Delhi in India

Abstract: Rising concentration of air pollution and its associated health effects is rapidly increasing in India, and Delhi, being the capital city, has drawn our attention in recent years. This study was designed to analyze the spatial and temporal variations of particulate matter (PM2.5) concentrations in a mega city, Delhi. The daily PM2.5 concentrations monitored by the Central Pollution Control Board (CPCB), New Delhi during November 2016 to October 2017 in different locations distributed in the region of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 19 publications
4
28
1
Order By: Relevance
“…The relatively small size of PMs, especially the PMs with a diameter smaller than 2.5 um (PM2.5) allows them to be inhaled into deeper respiratory tracts, even into the circulatory system, and to induce detrimental health effects within the cardiopulmonary system (Brook et al, 2004;Almendra et al, 2017). While developed countries, such as the United States and Japan, displayed acceptable levels of ambient PM, some areas of the world displayed relatively high levels, far beyond the healthy levels set by the World Health Organization (Puett et al, 2011;Zhou et al, 2015;Gorai et al, 2018;Khan et al, 2018), posing a significant threat to human health. PM exposure has been associated with cardiovascular diseases (Ensor et al, 2013;Sohn et al, 2016) and cardiovascularrelated mortality (Zhang C. et al, 2018;Hvidtfeldt et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The relatively small size of PMs, especially the PMs with a diameter smaller than 2.5 um (PM2.5) allows them to be inhaled into deeper respiratory tracts, even into the circulatory system, and to induce detrimental health effects within the cardiopulmonary system (Brook et al, 2004;Almendra et al, 2017). While developed countries, such as the United States and Japan, displayed acceptable levels of ambient PM, some areas of the world displayed relatively high levels, far beyond the healthy levels set by the World Health Organization (Puett et al, 2011;Zhou et al, 2015;Gorai et al, 2018;Khan et al, 2018), posing a significant threat to human health. PM exposure has been associated with cardiovascular diseases (Ensor et al, 2013;Sohn et al, 2016) and cardiovascularrelated mortality (Zhang C. et al, 2018;Hvidtfeldt et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the transferability of these pre-determined calibrations at collocation sites to new deployment sites is questionable as cali-bration factors typically vary with operating conditions such as PM mass concentrations, relative humidity (RH), temperature, and aerosol optical properties (Holstius et al, 2014;Austin et al, 2015;Wang et al, 2015;Lewis and Edwards, 2016;Crilley et al, 2018;Jayaratne et al, 2018;Zheng et al, 2018). Complicating this further, the pre-generated calibration curves may only apply for a short term as the stability of low-cost sensors can develop drift or degrade over time (Lewis and Edwards, 2016;Jiao et al, 2016;Hagler et al, 2018). Routine recalibrations which require frequent transit of the deployed sensors between the field and the reference sites are not only too labor intensive for a large-scale network but also still cannot address the impact of urban heterogeneity of ambient conditions on calibration models (Kizel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The Air Quality Index (AQI) of the US Environmental Protection Agency (US EPA) is a widely used index which gives details about the daily air quality status [35]. In the present work, with the principal aim to investigate the possible relationship between the configured PM burden (mass, chemical composition) and the corresponding health effects, the USEPA Air Quality Index (AQI) for PM 2.5 was applied.…”
Section: Health Riskmentioning
confidence: 99%
“…In the present work, with the principal aim to investigate the possible relationship between the configured PM burden (mass, chemical composition) and the corresponding health effects, the USEPA Air Quality Index (AQI) for PM 2.5 was applied. Details about the specific methodology, the breakpoints for the PM 2.5 concentrations, the ranges of the PM 2.5 -AQI categories and the possible health consequences are given in EPA 1999, [36] and Gorai et al [35]. Dimitriou et al [37] found that AQI in Athens is mainly affected by PM (by 72%) and only 28% by ozone with the contribution of other pollutants being negligible.…”
Section: Health Riskmentioning
confidence: 99%